Count Adam G. de Gurowski papers - De Gurowski, Adam G., count, 1805-1866.; Bing, Julius
Correspondence, notes and drafts of books and articles, lectures, printed matter, photographs, and other papers relating primarily to de Gurowski's study of America, Code Napoléon (French civil law), Crimean War, ethnology, philosophy of history, Hungary, Japhetians, New York, N.Y., Poland, Roman law, Russia, and history of slavery. Includes manuscripts of Julius Bing's autobiography and his biography of de Gurowski.
Polish scholar and author; advocate of Panslavism.
Collection material in English and French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Japheth -- (Biblical figure); Civil law -- France; Crimean War, 1853-1856.; Ethnology; History -- Philosophy; Slavery; Panslavism; Roman law; America; Hungary; New York (N.Y.); Poland; Russia; Authors; Scholars